Transição paradigmática entre os pressupostos da simplicidade e da complexidade: por uma defensoria pública sistêmica - Costa, Alex Thiébaut Menezes Nunes da (2022)
The research focuses on the challenges of thinking about the transition between the hegemonic Cartesian paradigm, in which the assumption of simplicity prevails, and a new paradigm of legal science, which encompasses social complexity and how the Public Defender institution is situated in this context. of transformation. The work is structured in three chapters. In the first one, we will try to present the rationalism coming from the work of René Descartes, who changed the scholastic paradigm until then hegemonic, based on theological knowledge, to another one in which simplicity prevails, as well as analyzing the emergence of the scientificity of social studies with the help of positivism. of Auguste Comte and its ramification for legal science, through the work of Hans Kelsen and his Pure Theory of Law, of fundamental importance for the creation of the bases of Law as a science. The chapter ends with the critique of modern reason made by Boaventura de Sousa Santos and presenting the institutional normative history of the Public Defender's Office. In the second chapter, the transformations experienced by the Public Defender's Office, both doctrinal and legislative, will be exposed, especially since the promulgation of the Federal Constitution of 1988, the edition of its National Organic Law and its respective changes, presenting the main characteristics, principles and institutional functions. , objectives, guarantees and prerogatives of the members of this institution that has the constitutional mission of guaranteeing free access to justice for the vulnerable. In the third chapter, we will deal with the paradigmatic transition between the assumptions of simplicity and complexity in legal science, placing the Public Defender's Office as one of the protagonists of this transformation, listing the benefits of using systemic thinking as a means of effecting and evolving the provision of assistance full and free legal assistance to groups made invisible